Analysis of Mechanical Properties of Basalt Hybrid Woven Fabrics (Journal of Fiber Bioengineering and Informatics, 2016)
Textiles applications in technical area is one of the imperative subjects in present time. Applicationof textiles in various fields especially in protective garments application is increasing day by day. Theobjective of this work is to evaluate and discover the effect of fiber and structure on tensile and dynamicmechanical properties of hybrid and non-hybrid basalt structures. This work deals with the study ofthe mechanical properties of woven fabrics in relation to fiber and weave. In this study, investigativeexperiments are carried out to find out the static and dynamic mechanical behaviour of Basalt ⁄ Polyester(B ⁄ PET) and Basalt ⁄ Polypropylen (B ⁄ PP) fibre hybrid woven and non-hybrid woven fabric. Threetypes of weaves are used i.e. Plain (PW), Matt (MW) and 1 ⁄ 3 Twill (TW) for hybrid and non-hybridstructures respectively. The tensile testing of all the woven fabric specimens is carried out. The discussionof results is in terms of fibre effect and woven geometry. The exposure of fabrics to increasing temperatureis beneficial to their mechanical properties and performance. The dynamic mechanical analysis exhibitsa rise in storage modulus. It indicates a lower damping and higher stiffness ratio in hybrid fabrics. Thesefabrics can be used for temperature resistant applications and in composites.